Indonesia's Diplomatic Strategy in Promoting Tourism in Singapore as an Effort for Indonesia's Economic Recovery in 2022 - Sri Dewi Lestari (UNIDA GONTOR, 2021)
In this study, the authors discuss Indonesia's diplomatic strategy in promoting tourism in Singapore in 2022after the subside of Covid-19. Indonesia considers Singapore as one of the potential countries to carry out tourismpromotion, because there are three influencing factors, namely: Community, Geographic, and Market as calculationsfor Indonesia. Indonesia also sees that Singapore is the main key for its tourism because it is a connecting country forAsian and European countries when they want to visit Indonesia. The purpose of this research is to find out howIndonesia's diplomacy strategy is in promoting tourism in Singapore in 2022 by using the concept of culturaldiplomacy as a tool in analyzing this strategy. This study uses a qualitative descriptive method and uses a docume ntbased literature study with miles and Huberman analysis techniques. The results of this study indicate that Indonesiauses tourism to achieve its national interests as attracting Singaporean tourist visits in an effort to recover the economyafter the Covid-19 pandemic, by carrying out several strategies such as conducting a travel bubble cooperation whichreopened flight and shipping routes for the two countries followed by cooperation marketing collaboration andorganizing sales missions in Singapore. In addition, Indonesia and Singapore also carried out a youth exchangeprogram as one of their cultural diplomacy strategies. With this cultural diplomacy strategy,